2005
DOI: 10.1021/jp058124r
|View full text |Cite
|
Sign up to set email alerts
|

Nondissociative Chemisorption of Short Chain Alkanethiols on Au(111)

Abstract: The adsorption of methanethiol and n-propanethiol on the Au(111) surface has been studied by temperature-programmed desorption (TPD), Auger electron spectroscopy (AES), and low-temperature scanning tunneling microscopy (LT-STM). Methanethiol desorbs molecularly from the chemisorbed monolayer at temperatures below 220 K in three overlapping desorption processes. No evidence for S-H or C-S bond cleavage has been found on the basis of three types of observations: (1) A mixture of chemisorbed CH3SD and CD3SH does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
118
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 31 publications
13
118
0
2
Order By: Relevance
“…In the 2 3 p phase, the Au-thiolate complex occupies both fcc and hcp sites, the energy of these local sites is essentially identical, and the barrier for movement between them is small; intermolecular interactions then can then play a far greater role in the self-organization. The fact that the formation of Authiolate surface complexes accompanies the Au/thiol surface reaction must also influence the reaction dynamics, and is clearly consistent with the recent finding that the deprotonation reaction occurs at defects sites on the surface [28]. Finally, our observation of the same behavior in a completely different complex phase of tertiarybutlythiolate on Au(111) (for which steric hindrance precludes the formation of the 3 p phase), suggests the adatom-thiolate moiety may also occur in the far wider class of (functionalized) thiolate SAMs on Au(111).…”
Section: Fig 1 (Color Online) Side View Of Ausupporting
confidence: 88%
“…In the 2 3 p phase, the Au-thiolate complex occupies both fcc and hcp sites, the energy of these local sites is essentially identical, and the barrier for movement between them is small; intermolecular interactions then can then play a far greater role in the self-organization. The fact that the formation of Authiolate surface complexes accompanies the Au/thiol surface reaction must also influence the reaction dynamics, and is clearly consistent with the recent finding that the deprotonation reaction occurs at defects sites on the surface [28]. Finally, our observation of the same behavior in a completely different complex phase of tertiarybutlythiolate on Au(111) (for which steric hindrance precludes the formation of the 3 p phase), suggests the adatom-thiolate moiety may also occur in the far wider class of (functionalized) thiolate SAMs on Au(111).…”
Section: Fig 1 (Color Online) Side View Of Ausupporting
confidence: 88%
“…Thiol-based SAMs are also sensitive to heating, and their thermal stability is limited to 400 K [101]. Above this temperature, thiol molecules start to desorb in the form of disulfides, suggesting that the Au-S bond is weaker than the S-C bond of thiols [102]. Some discrepancy, however, exists about the thermal stability of monolayers of thiol [103].…”
Section: Electrode Functionalizationmentioning
confidence: 99%
“…[6], [7]. Kondoh et al observed that methanethiolate occupies the atop site on the perfect Au(111) surface [17], but here our adsorbate is methanethiol.…”
mentioning
confidence: 97%